Methods of granulation of molten slag and use of granulated slag water - Kravchenko, V. P.; Karlikova, Ya. P.; Gankevich, V. F.; Polushyna, M. V.; Livak, O. V. (Видавництво НГУ, 2019)
Relevance of the topic. One of the most important processes in a blast furnace, determined its operation, is slag formation. Metallurgical slag is the most valuable coproduct material. More than 50% of the volume of molten slag obtained in a blast furnace is processed into granulated slag. Crushed stone, pumice-stone, slag wool (high-alumina clinker) and cast products (in small quantities) are also produced from the blast furnace slag. Nowadays in Ukraine about 80-85% of blast furnace slag is being processed. Part of the slag is shipped to dumps, which causes environmental problems such as pollution of land, air, water. Therefore, the use and processing of slag, as a valuable byproduct, are urgent problems of our time. Granulated Slag Production. Granulation is the process of transformation of molten slag into glassy granules by quenching with water, steam, air or another gas. There are three systems of granulation process: water, semi-dry and dry. Water granulation methods are most commonly used in the production of granulated slag. During the water granulation the slag granules are formed due to the property of molten slag to crack under the influence of thermal stresses and spray by microexplosions when the melt contacts with water. The water granulation production of slag is the oldest and simplest one and is divided into basin and grooved methods.
Keywords: кафедра технологічного інжинірингу переробки матеріалів; збагачення корисних копалин 2019; наукова публікація НТУ "ДП" 2019; загальні питання технологій збагачення